On the Reception of the French Version of Cupid and Psyche Plot in the Poem of Ippolit Bogdanovich “Dushenka” (1783): Рецепция французской версии традиционного сюжета об Амуре и Психее в поэме И. Ф. Богдановича «Душенька» (1783) - Kotaridi, Yuliya (Przegląd Wschodnioeuropejski, 2019)
The subject of this paper is the transformation of poetics of Cupid and Psyche plot in its national and historical modifications in French and Russian literatures of the 17th–18th centuries. The methodology of the analysis is based on mythological studies (K. Levi-Strauss, J. Frazer, A. N. Veselovsky, A. F. Losev) and genre studies (M. M. Bakhtin, S. S. Averintsev, E. M. Meletinsky, etc.). This paper examines the genre of J. de La Fontaine’s and his follower Ippolit Bogdanovich’s versions of the plot and the interrelation of various literary styles in their poetics. The genre of the French and Russian versions absorbs the elements of Classicism, Baroque and Rococo which are combined in syncretic unity. The transformation of the tale of Cupid and Psyche leads La Fontaine and Bogdanovich to the creation of a hybrid genre in which the initial version of the plot is exposed to travesty and revaluation.